EVALUATING PUBLIC EDUCATION EXPENDITURE AND ITS EFFECTIVENESS IN ZILHA PARISHAD SCHOOLS OF DHULE DISTRICT - Ms. Usha Ashok Manore, Prof. Vijay B. Mante (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
This study evaluates the effectiveness of public education expenditure in Zilha Parishad schools in Dhule District, Maharashtra. It explores how funds are distributed and their impact on school infrastructure, teaching quality, and student performance. By analyzing budget data and educational outcomes, the research identifies discrepancies in funding allocation and areas where investment is insufficient. The findings suggest that despite substantial expenditure, the impact on student achievement and retention remains limited. The paper concludes with recommendations for improving the efficiency of education spending to enhance overall educational outcomes in the district.